Mekanisme Pertahanan Mukokutan terhadap Infeksi Candida: Analisis - Adelia Wuri Pramudita; Harijono Kariosentono; Annisa Marsha Evanti; Zilpa Widyastuti (PT Kalbe Farma Tbk., 2025)
Candida albicans is a commensal organism that can may become invasive and fatal under certain circumstances. Several genetic variations in the human genome towards susceptibility to Candida infections have been identified. There are a number of genes associated with Candida virulence factors, host environment, and immune response. C-type lectin receptors (CLRs) are characterized by leucine-rich and nucleotidebinding domains that can detect intracellular signals through various types of cytoplasmic domains. CLRs are family of PRRs that bind glycan through recognition of extracellular carbohydrate and mediate intracellular signaling through various type of cellular domains, resulting in a decrease of neutrophils and facilitating the occurrence of fungal infections. This study review the genetic determinant of defense mechanisms and immune deficiencies against Candida infection.